Repetitive transcranial magnetic stimulation for generalised anxiety disorder: A pilot randomised, double-blind, sham-controlled trial. (September 2016) - Diefenbach, Gretchen J.; Bragdon, Laura B.; Zertuche, Luis; Hyatt, Christopher J.; Hallion, Lauren S.; Tolin, David F.; Goethe, John W.; Assaf, Michal
Abstract : Background: Repetitive transcranial magnetic stimulation (rTMS) holds promise for treating generalised anxiety disorder (GAD) but has only been studied in uncontrolled research. Aims: This is the first randomised controlled trial (clinicaltrials.gov: NCT01659736) to investigate the efficacy and neural correlates of rTMS in GAD. Method: Twenty five participants (active n = 13; sham, n = 12) enrolled. rTMS was targeted at the right dorsolateral prefrontal cortex (DLPFC, 1 Hz, 90% resting motor threshold). Results: Response and remission rates were higher in the active v. sham groups and there were significant group × time interactions for anxiety, worry and depressive symptoms, favouring active v. sham. In addition, right DLPFC activation during a decision-making gambling task increased at post-treatment for active rTMS only, and changes in neuroactivation correlated significantly with changes in worry symptoms. Conclusions: Findings provide preliminary evidence that rTMS may improve GAD symptoms in association with modifying neural activity in the stimulation site.